Surviving Job Loss Stress: Examining Dyadic Coping Process across Time. Issue 2 (3rd April 2021) - Schauss, Eraina; Hawes, Kiersten; Ellmo, Frances; Brasfield, Michelle W.
Abstract: The primary purpose of this study was to investigate how couples cope with the stress of job loss. We examined dyadic coping processes of social support and undermining over time for couples experiencing job loss and subsequent unemployment. The research design was a longitudinal field study of 357 individuals seeking reemployment and their respective partners. Data were collected at four times over the course of approximately a year. Results show a steady decline in support among jobseekers and their partners over time. Additionally, social support was found to be a significant predictor of inverse changes in undermining across all measured time periods. Results are discussed in connection with counseling intervention strategies for couples.